Technology Based Self-Reflection As A Tool For Enhancing Professional Development: A Pre-Service English Teacher Perception - Murny, Murny; Ruliany, Suci; Martius, Martius; Roza, Ellya; Nurhasnawati, Nurhasnawati (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Self-reflection is one way that can apply to the pre-service teachers to produce an excellent teaching-learning process. This study aims to investigate the pre-service teacher's perception of self-reflection by using technology and what efforts they made to provide self-reflection by using technology. The design of this study is descriptive quantitative and qualitative research. This research involved twenty pre-service English teachers in Riau Province. The data was collected through e-questionnaires and individual interviews, which obtained pre-service teacher perception toward self-reflection by using technology and the efforts that integrated it with technology. After the data analysed, it found that pre-service English teacher has good perception toward self-reflection but still need improvement. The study underscores the importance of integrating technology into professional development initiatives and highlights the benefits of self-reflection in promoting teacher growth and effectiveness. These findings have implications for teacher education programs and can inform the design and implementation of professional development strategies to better support pre-service English teachers in their journey towards becoming proficient educators.